FACTORS AND TOOLS FOR PRESERVING AND SUPPORTING BUSINESS IN WAR CONDITIONS: FINANCIAL AND INSURANCE ASPECTS - FURSOVA, Olena; HREBINSKA, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article considers the aspects of ensuring the viability of economic entities in the critically difficult conditions of a full-scale war. As stated, in world practice, the fact of the functioning of the national economy of a country under military aggression, and even more so the preservation of the viability of economic agents, is considered paradoxical a priori. However, this has been a common practice for Ukraine for three years. The purpose of the study is to identify the factors and justify the tools of the state and corporate policy of preserving and supporting Ukrainian business in the conditions of war with the use of financial and insurance means for such purposes. Threats to the financial security of domestic economic entities in war conditions were determined by such components of security as credit, insurance, monetary, budgetary and tax, investment and fund security. Based on the same components, a policy toolkit for supporting domestic business in wartime conditions was developed, in particular in the sense of financial and insurance aspects of regulation. It was established that in the conditions of a full-scale war, the following became the dominant threats to the financial security of domestic business entities: freezing of investment projects, loss of foreign investment, destruction of facilities (investment component of financial security of enterprises); complication of attracting financial and credit resources, growth of external and internal debt, difficulty of attracting credit funds (credit component); devaluation of the national monetary unit, slowdown in the circulation of funds, difficulties in settlements with counterparties (monetary component); increase in the level of tax liabilities, decrease in the level of budget investment, delays in calculations (budget and tax component); problems of securities issuance, a decrease in the level of dividend distribution, the decline of the country’s stock system (stock component); aggravation of the problems of insurance of military risks, increase in the cost of insurance services, actualization of the problems of internal and self-insurance (insurance component). Policy instruments for strengthening the financial security of business in wartime conditions have been defined. This is the diversification of sources of investment formation, consideration of investment options abroad, however, for the production of products in the domestic market; activation of cooperation programs between enterprises to replace credit resources, optimization of internal and external debt, replacement of part of operations in foreign currency, formation of insurance and reserve funds, "decomposition" of business into separate components, detinization and legalization of business, proactive state policy in this area, use of public investment instruments, improvement of conditions for purchasing OVDP bonds, diversification of state securities, active investment policy of enterprises, improvement of war risk insurance instruments, active involvement of foreign companies to the domestic insurance market.
Keywords: business entities; enterprises; war; survival; security; sustainability; factors; security tools; preservation and support of business; finance; insurance